2000
DOI: 10.1002/1099-0984(200011/12)14:6<497::aid-per379>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The hierarchical structure of common Turkish person-descriptive adjectives

Abstract: Findings from analyses of self-descriptions by 631 native speakers of Turkish, using 498 familiar Turkish person-descriptive adjectives, are compared to those of Saucier (1997), who analyzed 500 familiar English adjectives. In the total item pools in both studies, variants of the English/German `Big-Five' factors were recovered, along with a broad Attractiveness factor and another factor composed of items of extremely low endorsement rates. Moreover, in both studies when the item pools were restricted to terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 14 publications
4
78
1
2
Order By: Relevance
“…We should note that additional lexical investigations of person‐descriptive terms have also been carried out in languages such as Filipino or Tagalog (e.g., Church, Katigbak, & Reyes, 1998) and Turkish (Goldberg & Somer, 2000). But because these projects have included non‐personality‐descriptive terms within their variable sets, such as purely evaluative terms of insult or praise and/or terms describing physical appearance, their results are less directly comparable to those of the other projects described here.…”
Section: Results Of Lexical Studies Across Languages: Emergence Of Thmentioning
confidence: 99%
“…We should note that additional lexical investigations of person‐descriptive terms have also been carried out in languages such as Filipino or Tagalog (e.g., Church, Katigbak, & Reyes, 1998) and Turkish (Goldberg & Somer, 2000). But because these projects have included non‐personality‐descriptive terms within their variable sets, such as purely evaluative terms of insult or praise and/or terms describing physical appearance, their results are less directly comparable to those of the other projects described here.…”
Section: Results Of Lexical Studies Across Languages: Emergence Of Thmentioning
confidence: 99%
“…Two‐factor solutions from several lexical studies also suggest a consistent pattern: One factor includes attributes associated with positively valued dynamic qualities and individual ascendancy, whereas the other factor includes attributes associated with social self‐regulation, socialization, solidarity, and community cohesion (De Raad & Barelds, 2008; Di Blas & Forzi, 1999; Goldberg & Somer, 2000; Hřebíčková, Ostendorf, Osecká, & Čermák, 1999; Saucier, 1997, 2003). Such a factor structure resembles that embodied in the theoretical model of Bakan (1966), who labeled the two factors Agency and Communion.…”
Section: What We Learn From Natural‐language Personality Descriptionsmentioning
confidence: 87%
“…Several lexical studies have reported evidence about factor solutions containing only one factor (Boies et al., 2001; De Raad & Barelds, 2008; Di Blas & Forzi, 1999; Goldberg & Somer, 2000; Saucier, 1997, 2003). The findings from these studies have been quite consistent, and would likely be confirmed by data from all studies upon examination.…”
Section: What We Learn From Natural‐language Personality Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Turkish language, a member of the Altaic group, was studied by Somer and Goldberg (1999;Goldberg & Somer, 2000). Five native speakers culled 2,200 person-descriptive adjectives from three modern abridged Turkish dictionaries.…”
Section: Studies In Turkishmentioning
confidence: 99%